LEARNING ENGLISH WITH TECHNOLOGY (A STUDY IN CROSS CULTURE UNDERSTANDING COURSE) - Zaiturrahmi, Zaiturrahmi; Fitriani, Naria; Liani, Jannatul; Ratkovic, Nada (Dharmas Education Journal (DE_Journal), 2023)
The Integration of information and Communication Technology (ICT) has been expanding rapidly now day. So does in learning English, especially in Cross Culture Understanding course. This study encompassed on students’ experiences on using google classroom. This research categorized as qualitative descriptive method since the researcher attempted systematically to describe a situation, problem, phenomenon about implementation of Google classroom application. The finding showed easy to acces; allows students to submit assignments electronically, which can be convenient and reduce the need for physical paperwork; Students can interact with their teachers and peers through announcements, comments, and class discussions. This feature helps maintain a sense of community and engagement in the virtual classroom. On the other hand, there are some problems also such as bad internet connection, difficult to submit assignment on time, and sufficient storage to run.